Nongovernmental Organizations in the Design and Implementation of Social Forestry Programs in Indonesia: Interests, Power and Strategies - Ragandhi, Arsad; Hadna, Agus Heruanto; Setiadi, Setiadi; Maryudi, Ahmad (Forest and Society, 2025)
Many social forestry projects have failed to produce expected outcomes. In many cases, they do not suit specific local contexts, problems, and needs because they only articulate the interests of powerful actors outside local communities. In this study, we examine how nongovernmental organizations (NGOs) affect social forestry implementation. In many cases, NGOs are characterized as benevolent actors, often claiming to represent voiceless groups, including poor local communities, in the social forestry context. We are specifically interested in analyzing the ways by which the studied NGOs have shaped the implementation of social forestry models in the forests managed by the state company of Perhutani. We focus on how the NGOs operate and their motivation and strategies nuanced around their power relations vis-à-vis the state company, how they have been shaped and readjusted. We found that due to competition for funding some of the analyzed NGOs were ably persuaded to alter their initial idealistic motivation of serving the best interests of local communities, while the others were simply motivated by financial self-gains from the resource-full state company. Even when the central government pushed the company to implement an innovative scheme, with greater rights and access granted to local communities, NGOs continued to favor the company’s interest by successfully persuading locals to continue with the old social forestry scheme. The study findings enhance the growing literature on the diverse roles of NGOs as interest groups in forest/environmental policies beyond the old characterization.